Quantifying asbestos in lung tissue: what debate?. Issue 6 (29th June 2017) - Nemery, Benoit; Nuyts, Valerie; Nackaerts, Kristiaan
This issue of the European Respiratory Journal contains an article entitled "The asbestos fibre burden in human lungs: new insights into the chrysotile debate" by Feder et al . [1]. Although respiratory physicians are very familiar with the devastating health effects of past asbestos exposure, many nonspecialist readers probably wonder what this "chrysotile debate" might be and how this article provides new insights into it. The debate involves the biopersistence and, hence, harmfulness of chrysotile as opposed to other types of asbestos. As is often the case with environmental issues, the implications of the debate are not just scientific. The implications of the "chrysotile debate" reach far beyond scientific circles http://ow.ly/OUNj30bPSGU